Smart Irrigation Controllers: Operation of Evapotranspiration-Based Controllers - Michael D. Dukes; Mary L. Shedd; Stacia L. Davis (EDIS)
AE446, a 5-page illustrated fact sheet by Michael D. Dukes, Mary L. Shedd, and Stacia L. Davis, is part of the Smart Irrigation Controllers series. It presents the operational techniques of several commercially available evapotranspiration (ET) controllers that are being studied at the University of Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, February 2009.